Challenges to volunteers' participation toward primary health-care system and providing managerial solutions - Mostafa Alimehr; Asgar Aghaei Hashjin (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The role of citizens' participation in the process of social, economic, and cultural development is necessary. Institutionalizing this role is inevitable to identify priorities and also planning, implementing, and evaluating health services. This study aimed to identify challenges ahead of volunteers' participation toward primary health-care (PHC) system and providing managerial solutions. MATERIALS AND METHOD: The study employed a qualitative research design. The data were collected via semi-structured interviews with key experts in the Ministry of Health, university education and health promotion officials, education experts, health center staff, and health volunteers. Then, a focused group discussion method was employed to provide solutions. The participants were selected via the purposive sampling method. The qualitative data were analyzed using a thematic analysis method. RESULTS: The analyzed data were categorized into 6 main themes and 24 subthemes. The most important challenges were categorized into six temporal, management, education, quality of services, motivation, and infrastructural themes. Allocating special funds for the health volunteer program, paying attention to the problems of the health workers, providing motivational programs, holding regular retraining courses and providing educational software for health volunteers, holding regular training courses for health trainers and volunteers, and supporting the health volunteer program are among the solutions. CONCLUSION: The present study showed that the health volunteer program in the PHC system faces several challenges, most of which are organizational and managerial ones. Therefore, a multifaceted approach should be used to improve the participation of health volunteers. In addition to motivational factors, factors such as allocating proper resources, empowering trainers, and mobilizing the community should be also considered. It seems that interaction among health system, people, and health volunteers should be improved.